2020
DOI: 10.1007/s10340-020-01309-4
|View full text |Cite
|
Sign up to set email alerts
|

Insect pest monitoring with camera-equipped traps: strengths and limitations

Abstract: Integrated pest management relies on insect pest monitoring to support the decision of counteracting a given level of infestation and to select the adequate control method. The classic monitoring approach of insect pests is based on placing in single infested areas a series of traps that are checked by human operators on a temporal basis. This strategy requires high labor cost and provides poor spatial and temporal resolution achievable by single operators. The adoption of image sensors to monitor insect pests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(117 citation statements)
references
References 64 publications
(101 reference statements)
0
94
0
2
Order By: Relevance
“…The latest high-performance CNN-based detection and classification models require a large number of images to optimize their numerous parameters. Only a few practical and large datasets currently exist for insect detection because setting many cameras to capture numerous insects in various field backgrounds is costly (Preti et al, 2020). Although we collected hundreds of flea beetle images, merely thirty im-516 ages were considered effective samples for each species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latest high-performance CNN-based detection and classification models require a large number of images to optimize their numerous parameters. Only a few practical and large datasets currently exist for insect detection because setting many cameras to capture numerous insects in various field backgrounds is costly (Preti et al, 2020). Although we collected hundreds of flea beetle images, merely thirty im-516 ages were considered effective samples for each species.…”
Section: Discussionmentioning
confidence: 99%
“…Insects are some of the most abundant groups of animals 2 in the terrestrial ecosystem. Rapid and accurate identifica-3 tion of insect species is essential for pest management (Park et al, 2020;Preti et al, 2020) and species-level identifica-5 tion in biodiversity monitoring (Hogeweg et al, 2019;Høye 6 et al, 2021). To augment the expertise in insect taxonomy takimoto@c.oka-pu.ac.jp (H. Takimoto) ORCID(s): 0000-0002-8795-7109 (H. Takimoto); 0000-0002-6466-723X (Y. Sato); 0000-0001-7891-5049 (A.J.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we selected the common solid food lures of protein baits for all the species of citrus fly pests, and they were processed as fine particles that were evenly adsorbed to the sticky surface of the yellow paper. The previous works [39,40] have proved that the incorporation of appropriate attractants into the surface of sticky traps will efficiently capture flies.…”
Section: Processing Of Yellow Sticky Trapmentioning
confidence: 99%
“…This technique have gained popularity because it allows for non‐intrusive observations at large spatiotemporal scales and constant sampling effort (Rovero & Zimmermann, 2016; Wearn & Glover‐Kapfer, 2019). Recently, camera trapping of insects has become an active field of research and development but important technical limitations still persist (Pegoraro et al., 2020; Preti et al., 2021). First, although it has been reported that the passive thermal infrared motion sensor of commercial CT systems can be activated by large flying insects (Houlihan et al., 2019; Johnson & Raguso, 2016), most ectotherms, such as reptiles, amphibians and invertebrates, do not trigger motion sensors (Hobbs & Brehme, 2017).…”
Section: Introductionmentioning
confidence: 99%